We have to simplify : 6 (log c/log a) + 5 log(a) d - 7 log(a) b

Now we use the relation that log(a)b = log b / log a

6 (log c/log a) + 5 log(a) d - 7 log(a) b

=> 6(log c/ log a) + 5( log...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to simplify : 6 (log c/log a) + 5 log(a) d - 7 log(a) b

Now we use the relation that log(a)b = log b / log a

6 (log c/log a) + 5 log(a) d - 7 log(a) b

=> 6(log c/ log a) + 5( log d/ log a) - 7(log b/ log a)

=> (1/ log a)[ 6 log c + 5 log d - 7 log b)

use log a + log b = log (a*b) and a*log b = log (b^a)

=> (1/ log a)[ log c^6 + log d^5 - log b^7)

=> (1/ log a)[ log c^6*d^5 / b^7)

**Therefore the required result is (1/ log a)[ log (c^6*d^5 / b^7)]**